2013
DOI: 10.5560/znc.2013.68c0429
|View full text |Cite
|
Sign up to set email alerts
|

More Insight into the Chemical Composition of Greek Propolis; Differences and Similarities with Turkish Propolis

Abstract: We aimed to determine the differences and similarities between Greek and Turkish propolis with respect to their chemical composition given that the two countries have many similarities in floral biodiversity. We observed that: a) Greek propolis is different from the European-type propolis, having a high terpene content; therefore we can definitely characterize it as a Mediterranean type; b) the Turkish propolis collected along the coast line of the Aegean Sea is similiar to the examined Greek propolis; c) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…In ethanolic extract of propolis from Greece, it was reported a significant amount of flavonoids [mainly chrysin (2), pinocembrin (3), pinobanksin-3-O-acetate (4), galangin (9), and apigenin (15)] (Figure 1), and low amounts of phenolic acids and their esters. [17,64,[72][73][74][75] Terpenes [mainly totarol (36), isopimaric acid (42), βelemene (43), agathadiol (44), pimaric acid (34), isoagatholal (45) and isocupressic acid (32)] ( Figure 4) were also found with the exception of propolis from Nigrita that had high amounts of flavonoids and low amounts of phenolic acids and their esters, and without diterpenic compounds. [74] In addition, in the recent study of Kasiotis et al [76] it was not reported the presence of diterpenes in samples originating from Crete, Kos, and Amorgos (Greece), in the opposite of the finding of Popova et al, [75] where they have reported a relative high amount of this group of compounds in Crete samples.…”
Section: Southern European Coastmentioning
confidence: 99%
See 2 more Smart Citations
“…In ethanolic extract of propolis from Greece, it was reported a significant amount of flavonoids [mainly chrysin (2), pinocembrin (3), pinobanksin-3-O-acetate (4), galangin (9), and apigenin (15)] (Figure 1), and low amounts of phenolic acids and their esters. [17,64,[72][73][74][75] Terpenes [mainly totarol (36), isopimaric acid (42), βelemene (43), agathadiol (44), pimaric acid (34), isoagatholal (45) and isocupressic acid (32)] ( Figure 4) were also found with the exception of propolis from Nigrita that had high amounts of flavonoids and low amounts of phenolic acids and their esters, and without diterpenic compounds. [74] In addition, in the recent study of Kasiotis et al [76] it was not reported the presence of diterpenes in samples originating from Crete, Kos, and Amorgos (Greece), in the opposite of the finding of Popova et al, [75] where they have reported a relative high amount of this group of compounds in Crete samples.…”
Section: Southern European Coastmentioning
confidence: 99%
“…In other countries of Southern European Coast, such as Turkey, chemical composition of propolis has widely investigated by several authors. Quercetin (26), rutin (48), chrysin (2), pinocembrin (3), pinostrobin chalcone (49) and pinobanksin (1) and its derivatives were the most repeated flavonoids found in various simples of propolis from Turkey using different method of analysis such as gas chromatography-mass spectrometry (GC/MS), high-performance liquid chromatography (HPLC) and ultrahigh-performance liquid chromatography with a linear ion trap-high resolution Orbitrap mass spectrometry system (UHPLC-LTQ/orbitrap/MS/MS), [73,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] while Erdogan et al [96] have reported the presence of other flavonoids such as gallocatechin (50), epigallocatechin (51) and myricetin (52) in Anatolian propolis submitted to a pressurized liquid extraction. Other authors did not report the presence of flavonoids in Turkish propolis originating from Hatay, Ankara-Kazan and Mugla-Marmaris, [97 -100] at the same time they declared that terpenes such as αand β-eudesmol, isopimaric acid (42), dehydroabietic acid (53) and abietic acid (54) ( Figure 4) were included in the bioactive compounds of tested propolis samples.…”
Section: Southern European Coastmentioning
confidence: 99%
See 1 more Smart Citation
“…Kit pszczeli zw. propolisem, w skład którego wchodzą substancje żywiczne i balsamiczne oraz związki biologicznie czynne, pyłek, wosk, enzymy trawienne śliny robotnic oraz mechaniczne domieszki, jest wykorzystywany głównie do uszczelniania gniazda oraz polerowania komórek plastra (14,39). Aktywność przeciwbakteryjna propolisu związana jest z występowaniem w jego składzie flawonoidów: ganalginy, chryzyny i pinocembryny, a także hydroksykwasów i flawononów oraz kwasów tłuszczowych i pochodnych fenolokwasów.…”
Section: Ryc 1 Podział Typów Odporności Występującej U Pszczół Miodunclassified
“…Kwas kawowy, flawonony i flawony, wspólnie ze swoimi estrami, spowalniają rozwój bakterii pochodzenia zwierzęcego i roślinnego, które zanieczyszczają pyłek i nektar oraz wodę przynoszoną przez pszczoły zbieraczki do ula (38,43). Pszczoły oblepiają kitem wlot do ula, co stanowi także mechaniczną barierę przed wnikaniem patogenów do gniazda oraz potencjalnie przeciwdziała ich rozwojowi wewnątrz (14,45,85,87). Najnowsze badania udowadniają, że propolis ma również wpływ na ekspresję genów związanych z układem odpornościowym.…”
Section: Ryc 1 Podział Typów Odporności Występującej U Pszczół Miodunclassified